1985
DOI: 10.1002/jcp.1041230209
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid asymmetry in human erythrocyte ghosts

Abstract: Using phospholipase digestion and the fluorescent probe merocyanine 540 the maintenance of phospholipid asymmetry in the plasma membrane of human erythrocyte ghosts was investigated. Digestion with phospholipase A2 indicated that ghosts prepared in the presence of Mg++ as the only divalent cation retained the normal phospholipid asymmetry characteristic of intact erythrocytes. These ghosts, like normal erythrocytes, also failed to stain with merocyanine 540. However, the presence of as little as 5-10 microM Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 122 publications
(61 citation statements)
references
References 19 publications
1
60
0
Order By: Relevance
“…As in the case of inhibition of unactivated macrophages by RGDS, N-acetylglucosamine slowed the rate of uptake by activated macrophages ( Figure 2B). Both unactivated human monocyte-derived (McEvoy et al, 1986) and J774 (Pradhan et al, 1994) macrophages recognize erythrocytes with PS on their surface produced by abolishing the asymmetric transbilayer distribution of phospholipids in which PS is restricted to the inner leaflet of the membrane bilayer (Williamson et al, 1985). Since uptake of these lipid-symmetric erythrocytes is completely inhibitable by PS vesicles (Pradhan et al, 1994), unactivated macrophages recognize these erythrocytes by the PS exposed on their surface, and PS is the only signal they recognize.…”
Section: Resultsmentioning
confidence: 99%
“…As in the case of inhibition of unactivated macrophages by RGDS, N-acetylglucosamine slowed the rate of uptake by activated macrophages ( Figure 2B). Both unactivated human monocyte-derived (McEvoy et al, 1986) and J774 (Pradhan et al, 1994) macrophages recognize erythrocytes with PS on their surface produced by abolishing the asymmetric transbilayer distribution of phospholipids in which PS is restricted to the inner leaflet of the membrane bilayer (Williamson et al, 1985). Since uptake of these lipid-symmetric erythrocytes is completely inhibitable by PS vesicles (Pradhan et al, 1994), unactivated macrophages recognize these erythrocytes by the PS exposed on their surface, and PS is the only signal they recognize.…”
Section: Resultsmentioning
confidence: 99%
“…Reasoning that insertion of such cone-shaped lipids, known to differentially expand the membrane leaflet (18,(33)(34)(35), might accompany and even support G2A signaling (see below), we sought evidence using FM 1-43, a stain that preferentially inserts into loosely packed membranes to test for lyso-PL-induced plasma membrane perturbation (36,37). In support of this hypothesis, probing the plasma membrane of neutrophils at 1 min after stimulation with lyso-PLs showed that lyso-PC, lyso-PS, and lyso-PE enhanced FM 1-43 staining, whereas lyso-PA and oleic acid had minimal effects (Fig.…”
Section: Lyso-pl-induced G2a-dependent Signaling Is Associated With Mmentioning
confidence: 99%
“…When cytosolic levels of Ca 2+ are elevated in erythrocytes or platelets, PS appears on the cell surface within minutes. 43,44 Although Ca 2+ inactivates the translocase, 45 this event alone is insufficient to bring PS rapidly to the cell surface because of the slow rate of passive diffusion of phospholipids across the bilayer. 46 However, Ca 2+ also activates a non-specific, bi-directional lipid flipsite, distinct from the translocase and termed the scramblase.…”
Section: Mechanisms For Maintenance and Loss Of Ps Asymmetrymentioning
confidence: 99%